Search for magnetic monopoles and stable particles with high electric charges in √s=13 TeV pp collisions with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; et al. (Journal of high energy physics, 2023)
We present a search for magnetic monopoles and high-electric-charge objects using LHC Run 2 √s = 13 TeV proton-proton collisions recorded by the ATLAS detector. A total integrated luminosity of 138 fb−1 was collected by a specialized trigger. No highly ionizing particle candidate was observed. Considering the Drell-Yan and photon-fusion pair production mechanisms as benchmark models, cross-section upper limits are presented for spin-0 and spin-1/2 magnetic monopoles of magnetic charge 1gD and 2gD and for high-electric-charge objects of electric charge 20 ≤ |z| ≤ 100, for masses between 200 GeV and 4000 GeV. The search improves by approximately a factor of three the previous cross-section limits on the Drell-Yan production of magnetic monopoles and high-electric charge objects. Also, the first ATLAS limits on the photon-fusion pair production mechanism of magnetic monopoles and high-electric-charge objects are obtained.
*The ATLAS collaboration: G. Aad, L.M. Baltes, F. Bartels, M.M. Czurylo, S.J. Dittmeier, F. Del Rio, M. Dunford, S. Franchino, T. Junkermann, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und sehr viele weitere Personen]
Gesehen am 28.02.2025
Im Titel steht der Buchstabe "s" unter dem Wurzelsymbol